2008
DOI: 10.1080/09687760701850166
|View full text |Cite
|
Sign up to set email alerts
|

On campus, but out of class: an investigation into students' experiences of learning technologies in their self-directed study

Abstract: FrancesDeepwell f.deepwell@coventry.ac.uk This paper presents an investigation into how students studying at university engage actively with learning technology in their self-directed study time. The case study surveyed 250 students studying at undergraduate and postgraduate level from a purposive sample of departments within one institution. The study has also conducted focus groups and a number of in-depth follow-up interviews with respondents to the survey. In this article we explore three emerging aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…It may be, as other studies have found, that more academic guidance is needed to ensure that trainees, including those with high ICT skills, can use the technology effectively for independent learning (Deepwell and Malik 2008). Ellis et al (2007) determined that students benefit more from an online experience if they understand its purpose in relation to the task or learning outcome.…”
Section: Discussionmentioning
confidence: 99%
“…It may be, as other studies have found, that more academic guidance is needed to ensure that trainees, including those with high ICT skills, can use the technology effectively for independent learning (Deepwell and Malik 2008). Ellis et al (2007) determined that students benefit more from an online experience if they understand its purpose in relation to the task or learning outcome.…”
Section: Discussionmentioning
confidence: 99%
“…a mix of face-to-face and e-learning instruction (Deepwell and Malik 2008;Martins and Kellermann 2004). We study the effect of one dimension, from within a culture framework, on the introduction to blended learning for business undergraduates at a university in the United Arab Emirates (UAE).…”
Section: Introductionmentioning
confidence: 99%
“…They can suggest ways to use the mobile phone features outside the classroom. This is supported by Deepwell and Malik (2008) who stressed instructors' role in improving opportunities for students to use mobile technologies outside the classroom. Having said that, the instructors themselves may need training in this area to be able to help students ).…”
Section: Discussionmentioning
confidence: 98%